Proses Produksi dan Pengembangan UMKM Bolu Keju Sabilulungan - Agus Sutardi; Chyntia Ika Pertiwi; Fitria Anjarsari; Nunik Nur Asiah Jamil; Wahyudin Yusuf; Broderix Nicender Sorongan (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to determine the feasibility of the Sabilulungan Cheese Cake business based on Marketing Aspects, Technical and Operational Aspects, Management and Organizational Aspects, and Financial Aspects. The data collection method in this research is field study with descriptive methods. The data collection techniques used were interviews, observation and documentation. This research shows that the Sabilulungan Cheese Cake business development plan is declared feasible to implement in terms of Marketing Aspects, Technical and Operational Aspects, Management and Organizational Aspects, and Financial Aspects.